A fisioterapia como prática híbrida, as mudanças do currículo e o perfil profissional - Sumiya, Alberto [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This thesis is an approaching of Bruno Latour’s thought to the physiotherapist training issue regarding the concept of hybrid in order to contribute to deepening of the subject within physiotherapy practice. The analysis is focused on the relationship between nature and culture as parts of the same fabric, which are understood as separated to modern science. The hypothesis is that physiotherapy practice is hybrid, because it exposes the inevitable characteristics of mixtures. Therefore, the main objective of this study is to evidence from the curriculum changes the conditions that favor the proliferation of hybrids during the construction of professional identity. The research’s methodological procedures involved ethnography, documental analysis and interviews. The participating institutions were the University of Londrina (Brazil - Paraná) and Keele University (The UK). Data analysis inferred three categories: Professional profile: among curricula, guidelines and programme specifications; 2) Field of power: among interests, boundaries and possibilities of curricula structures; 3) Curriculum integration: the value of the mixtures in the physiotherapist education. The analysis of these categories was developed following a reasoning that demonstrated different conceptions about professional profile, evocating past, present and future. The field and its tensions, showed us resistances, disputes, differences of social capitals and how they might influence/modify the trajectory of the curricula. The curriculum integration condensed the expectations of explaining the physiotherapy knowledge as underpinned by hybrid concept, because it exposes the interaction of contents which leads to mixtures. The concept of hybrid represents the possibility of redefining the scientific relations of physiotherapy with its therapeutic practice, taking into account that human and technique’s domains cannot be separated clearly. Accept this mixture would...

Esta tese consiste na aproximação do pensamento de Bruno Latour à temática da formação do fisioterapeuta, no que se refere à utilização do conceito de híbrido para contribuir com o aprofundamento do assunto no âmbito das práticas da fisioterapia. A análise segue voltada para as relações entre natureza e cultura como partes de uma mesma tessitura, mas que se apresentam para a ciência moderna como separadas. A hipótese levantada é que o fazer da fisioterapia é híbrido, porque expõem as características inevitáveis das misturas. Portanto, o objetivo principal deste trabalho é evidenciar, a partir da análise de matrizes curriculares e perfis profissionais, as condições que favorecem a proliferação de híbridos durante a construção da identidade profissional. Os procedimentos metodológicos desta pesquisa envolveram etnografia, análise documental e entrevistas com professores. As instituições participantes foram a Universidade Estadual de Londrina (Brasil – Paraná) e a Keele University (The UK). A partir da análise dos dados depreendemos três categorias: 1) Perfil profissional: entre currículos, diretrizes e projetos pedagógicos; 2) Campo de poder: entre interesses, limites e possibilidades das estruturas curriculares; 3) Integração curricular: a valorização das misturas na formação do fisioterapeuta. A análise destas categorias desenvolveu-se seguindo uma linha de raciocínio, começando pela demonstração das diferentes concepções sobre o perfil profissional, evocando passado, presente e futuro. Passando em seguida, para o campo da fisioterapia e suas tensões, que deixaram claras as resistências, disputas e diferenças de capitais sociais e, como estes podem influenciar/modificar a trajetória que foi planejada pelas matrizes curriculares. A integração curricular, por sua vez, condensou as expectativas de explicar o conhecimento fisioterapêutico como alicerçado pelo conceito de híbrido, porque...
Keywords: Latour, Bruno - 1947; Universidade Estadual de Londrina; Physical therapy; Fisioterapia; Formação profissional; Fisioterapeutas - Formação; Universidades e faculdades - Curriculos